A Survey on Batch Training in Genetic Programming - Rosenfeld, Liah (2024)
Rosenfeld, L., & Vanneschi, L. (2025). A Survey on Batch Training in Genetic Programming. Genetic Programming And Evolvable Machines, 26, 1-28. Article 2. https://doi.org/10.1007/s10710-024-09501-6 --- Open access funding provided by FCT|FCCN (b-on). This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS (https://doi.org/10.54499/UIDB/04152/2020).